Pelaksanaan Layanan Bimbingan Klasikal untuk Meningkatkan Kemampuan Bijak Bersosial Media pada Siswa di SMP N 7 Bukittinggi - Vekta Juliantrik; Afrinaldi Afrinaldi; Whina Mutia (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
This research was motivated by the fact that students were still found to be less wise in using social media in their daily lives. For example, there are still students who spend a lot of time playing on social media, there are still students who make unfavorable comments on social media, and there are still students who make negative posts. This research aims to: (1) determine the level of student policy regarding social media (2) determine the level of student social media policy before being given classical guidance services. (3) find out whether or not classical guidance services are effective in increasing students' social media skills. This type of research is Pre-Experimental Design using the One Group Pretest-Posttest model. The population in this study was class VIII.2. The sample for this research was 27 people taken using a total sampling technique, which means that the entire population was the sample for the research. Data was collected using a scale for developing wise social media skills. Meanwhile, the data analysis technique used was the Wilcoxon test. The results of the research show that: (1) the wise description of students' social media before being given classical guidance services is in the medium category with a mean of 27.41. (2) after being given classical guidance services, they are in the medium category with an increasing score with a mean of 34.56. (3) classical tutoring services are effective in increasing students' social media skills. This statement is supported by the asymp sig (2-tailed) results, which obtained a value of 0.000, which means it is smaller than the α value of 0.05. So it can be said that Ha was accepted and Ho was rejected, meaning that classical guidance is effective in improving the social media skills of students at SMP N 7 Bukittinggi.